EVALUASI KINERJA APARATUR PEMERINTAH KOTA BANDAR LAMPUNG - Neta, Yulia (Fakultas Hukum Universitas Lampung, 2011)
The reseach is to study about the evaluation of government staff activities in bandar lampung city. The research metodology is normative juridiction and empirical juridiction. The result of research indicates that the government of bandar lampung city had productive human resource and it is hoped to give optimal contribution in the implememntation of regional goferentment. The government staff activities are well nowdays. there are six factors which influence the government staff activities such as the best model, job distribution, the objectivity of building government appliance, conducting reward/punishment, and specific skills (computer and english).